Gender Differences in Nutritional Status Among Adolescents in Sangihe Islands, Indonesia: A School-Based Cross-Sectional Study - Astri Mahihody; Jelita Siska Herlina Hinonaung; Grace Angel Wuaten; Meityn Disye Kasaluhe (Media of Health Research, 2026)
Adolescence is a critical phase of growth that requires higher nutritional intake, with different needs for males and females. Research on the relationship between gender and nutritional status among adolescents in Indonesia’s border island regions remains limited. This study aims to analyze the relationship between gender and nutritional status among adolescents at Manganitu State Junior High School No. 2 (SJHS 2), Sangihe Islands Regency. This cross-sectional study was conducted in October 2024 and included 139 students aged 12–15 years, selected through total sampling. Nutritional status was measured using the Age-Adjusted Body Mass Index (BMI-for-Age) based on the 2006 WHO standards and analyzed using the Chi-Square test (α = 0.05). The results showed that the majority of respondents had good nutritional status (79.1%); however, 5.8% were underweight, 5.0% were overweight, and 10.1% were obese. Statistical analysis revealed no significant association between gender and nutritional status: underweight (p = 1.000), normal weight (p = 0.436), overweight (p = 0.758). Gender is not a primary determinant of nutritional status in this population; behavioral and environmental factors such as dietary patterns and physical activity are thought to play a greater role. Routine anthropometric monitoring and nutrition education remain necessary given the continued presence of dual nutrition problems. Further research is recommended to more comprehensively explore the determinants of adolescents’ nutritional status in the Sangihe Islands region.